Clinical Research into Qufeng Zhidong Recipe Used to Treat 31 Children with Tic Disorder - 吴敏 肖光华 张建明 张欣 马博 王树霞 周亚兵 张婧延 (Journal of Traditional Chinese Medicine, 2010)
Objective： To assess the therapeutic effect and adverse reaction of Qufeng Zhidong Recipe （a recipe for dispelling wind to stop abnormal movement） used to treat children with tic disorder （TD）. Methods： The enrolled patients were randomized into a TCM group （31 cases） treated with Qufeng Zhidong Recipe and a Western medicine group （30 cases） treated with haloperidol and trihexyphenidyl. Two courses of treatment were observed with 12 weeks as one course. The therapeutic effect and adverse reaction were assessed with Yale Global Tic Severity Scale （YGTSS）, Tic Symptom Score Scale （TSSS）, TCM Syndrome Score Scale （TCMSSS）, Treatment Emergent Symptom Scale （TESS） and laboratory examinations. Results： The total effective rate was 100% in the TCM group and 60% in the Western medicine group with statistical significance in difference （P〈0.05）. All the scores in the TCM group were better than those in the Western medicine group （P〈0.05）. Conclusion： Qufeng Zhidong Recipe can obviously relieve the symptoms and signs of TD children without toxic side-effects.